Additive for ultralow-profile electrolytic copper foil, electrolyte, electrolytic copper foil preparation process, electrolytic copper foil and application of electrolytic copper foil
By optimizing the composition of electrolyte additives and the design of the anode plate, the efficient production of ultra-low profile electrolytic copper foil is achieved, solving the problems of complex manufacturing process and high cost in the prior art, and improving the production efficiency and mechanical properties of the copper foil.
Patent Information
- Application Number
- CN202411668982.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
AI Technical Summary
The existing ultra-low profile electrolytic copper foil is complex and costly, and the electrolyte components need to be adjusted independently between different processes, resulting in low production efficiency.
By optimizing the composition of electrolyte additives, a specific combination of brightener, wetting agent and leveling agent is adopted, and combined with the segmented design of the anode plate, the integration of electrolysis and surface treatment processes is achieved, and the process flow is simplified.
It realizes efficient production of ultra-low profile electrolytic copper foil, reduces production costs, simplifies the process flow, and improves the mechanical properties of copper foil.
Smart Images

Figure CN119530905A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic copper foil, and relates to an additive for ultra-low profile electrolytic copper foil, an electrolyte, a preparation process of the electrolytic copper foil, the electrolytic copper foil and the application of the electrolytic copper foil. Background Art
[0002] With the development of 5G communication technology, cloud storage and cloud computing, electronic products are moving towards a more miniaturized, lightweight, ultra-thin, intelligent and multifunctional direction, which poses unprecedented challenges to the comprehensive performance standards of electrolytic copper foil. Especially in the application of high-frequency and high-speed printed circuit boards (PCBs), the performance optimization of electrolytic copper foil has become a key link in ensuring the integrity and reliability of signal transmission.
[0003] When signals travel through high-speed circuits, they tend to be concentrated on the surface layer of the copper foil for transmission. This phenomenon is called the "skin effect." The skin effect causes the current signal to flow closer to the surface of the conductor. If the surface roughness of the copper foil is high, the path that the current needs to bypass will increase accordingly, which will cause higher conductor losses and seriously damage the integrity of the signal. Therefore, in order to alleviate the adverse effects of the skin effect on signal quality, the surface profile of the electrolytic copper foil must reach an unprecedented low level to meet the stringent requirements of high-frequency and high-speed PCBs for signal transmission.
[0004] Chinese invention patent CN114318429B discloses a nano-roughening electrolyte, method and product for ultra-low profile electrolytic copper foil, the nano-roughening electrolyte comprising an electrolyte and an additive, wherein the electrolyte is a copper sulfate sulfuric acid aqueous solution; the additive is a natural polysaccharide, specifically a mixture of one or more of fenugreek gum, guar gum, carob gum and carrageenan; also discloses a nano-roughening method for ultra-low profile electrolytic copper foil, comprising the following steps: step 1, heating the electrolyte and pumping it into a roughening electrolytic cell to prepare a raw foil; step 2, the raw foil is acid-washed and then enters the roughening electrolytic cell to prepare nano-copper nodules by electrodeposition; step 3, curing and anti-oxidation treatment to obtain the target copper foil; the copper foil has low roughness and high peel strength, and is suitable for use as a high-frequency and high-speed electrolytic copper foil.
[0005] However, in the above-mentioned technology, the manufacturing process of ultra-low profile electrolytic copper foil is roughly divided into two steps: raw foil preparation and surface treatment. Although it can enhance the bonding strength between copper foil and resin materials in copper clad laminates, thereby improving the stability and durability of the overall structure of copper clad laminates, the electrolyte composition used in the electrolytic raw foil process and the surface treatment process is significantly different, including copper ion concentration, sulfuric acid concentration, type and concentration of additives, etc., which all need to be adjusted independently. This not only makes the entire process flow lengthy and complicated, but also in the process of material flow between different processes, a large amount of waste copper foil is often generated, which greatly increases production costs. In addition, frequent adjustments to the electrolyte formula also increase the difficulty of production management and reduce production efficiency. Summary of the invention
[0006] The present invention aims at the problems existing in the prior art. The present invention provides an additive for ultra-low profile electrolytic copper foil, an electrolyte, a process for preparing electrolytic copper foil, an electrolytic copper foil and the application of the electrolytic copper foil. Starting from the electrolyte itself and the preparation process, the composition of the electrolyte additive is optimized and improved. The inventors found that compared with the additives in the prior art, the electrolytic copper foil prepared using the additive of the present invention has better low-profile characteristics; in addition, the present invention realizes the integration of electrolysis and surface treatment processes through the segmented design of the anode plate, and produces ultra-low profile electrolytic copper foil that meets the requirements, while shortening the process flow and effectively controlling the production cost.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] One of the purposes of the present invention is:
[0009] Provided is an additive for ultra-low profile electrolytic copper foil, comprising the following components: a brightener, a wetting agent and a leveling agent; the brightener is hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate; the wetting agent is hydroxyethyl cellulose and polyethylene glycol; the leveling agent is hydrolyzed collagen.
[0010] Furthermore, the mass ratio of the brightener, the wetting agent and the leveling agent is 1:(2-2.5):1.
[0011] Furthermore, the mass ratio of the hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate is (4-6):(8-12):(4-6).
[0012] Furthermore, the mass ratio of hydroxyethyl cellulose to polyethylene glycol is (16-30):(16-30).
[0013] Furthermore, the viscosity of the 2% hydroxyethyl cellulose aqueous solution at 20° C. is 500-700 mPa.s.
[0014] Furthermore, the molecular weight of the polyethylene glycol is 3000-5000Da.
[0015] Furthermore, the molecular weight of the hydrolyzed collagen is 2000-20000Da.
[0016] The second object of the present invention is:
[0017] Provided is an electrolyte for ultra-low profile electrolytic copper foil, comprising the following components: a copper sulfate electrolyte, chloride ions and any of the above-mentioned additives for ultra-low profile electrolytic copper foil.
[0018] Further, it includes: copper ion 65-75g / L, sulfuric acid 90-100g / L, chloride ion 5-10mg / L, hexylbenzylamine salt 4-6mg / L, polydisulfide propane sulfonate sodium 8-12mg / L, N,N-dimethyldithiocarboxamide propane sulfonate sodium 4-6mg / L, hydroxyethyl cellulose 16-30mg / L, polyethylene glycol 16-30mg / L and hydrolyzed collagen 16-24mg / L.
[0019] In some embodiments of the present invention, the preparation process of the electrolyte for ultra-low profile electrolytic copper foil (also known as raw foil electrolyte) is as follows: copper element, sulfuric acid and ultrapure water are added to a copper dissolving tank (wherein the purity of copper element is greater than 99.5% and the concentration of sulfuric acid is greater than 98%), and the copper is dissolved into a copper sulfate electrolyte, wherein the copper ion concentration is 65-75g / L and the sulfuric acid concentration is 90-100g / L; the copper sulfate electrolyte is then purified by multi-stage filtration and stored in a high-level tank; 38% concentrated hydrochloric acid is added to make the concentration of chloride ions in the raw foil electrolyte 5-10mg / L, and mixed evenly to obtain the product.
[0020] In the present invention, since the brightener adopts hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate with relatively small concentration and obvious grain refinement, the wetting agent adopts a smaller molecular weight combination to provide a better dispersion effect. In addition, in order to be suitable for the production of low-profile raw foil and to still have a leveling effect in the later stage of raw foil electrolysis and the roughening process, the leveling agent adopts hydrolyzed collagen with a wider molecular weight distribution.
[0021] The third object of the present invention is:
[0022] A process for preparing an ultra-low profile electrolytic copper foil is provided, comprising the following steps:
[0023] (1) mixing a copper sulfate electrolyte, chloride ions and an additive to obtain an electrolyte for ultra-low profile electrolytic copper foil;
[0024] (2) The electrolyte for ultra-low profile electrolytic copper foil is injected into the anode tank, and the anode plate is immersed in the electrolyte for ultra-low profile electrolytic copper foil. Current is passed through the cathode roller for continuous electrolysis to obtain the ultra-low profile electrolytic copper foil.
[0025] Furthermore, the anode plate includes a front anode plate, a middle anode plate and a rear anode plate.
[0026] Furthermore, the front section anode plate occupies 4 / 5 of the area of all anode plates, is 5-20mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle section anode plate occupies 1 / 20 of the area of all anode plates, is 2-5mm away from the cathode roller, and is between the front section anode plate and the rear section anode plate; the rear section anode plate occupies 3 / 20 of the area of all anode plates, is 6-10mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank.
[0027] In the present invention, the design of the front section, middle section and rear section of the anode plate corresponds to the steps of electrolytic preparation, roughening and curing of raw foil in the traditional electrolytic copper foil preparation process.
[0028] In the process of preparing copper foil by electrolysis on the surface of the cathode roller of the front-end anode plate, the improvement of additives (brightener, wetting agent and positioning agent) in the raw foil electrolyte, especially the selection of brightener and the synergistic effect of brightener, wetting agent and leveling agent, as well as its interaction with chloride ions, achieves the refinement of raw foil grains and the leveling of contour, thus providing a basis for achieving ultra-low contour electrolytic copper foil.
[0029] The copper acid concentration of the raw foil electrolyte will decrease after being consumed by the front anode plate for electrolysis. Combined with the middle anode plate design, a higher current density can be obtained to produce a roughened copper nodule. The copper acid concentration of the raw foil electrolyte will further decrease after being consumed by the front and middle anode plates for electrolysis. Combined with the lower current density of the rear anode plate, the roughened copper nodule can be further fixed, and finally an ultra-low profile electrolytic copper foil can be obtained.
[0030] The distances between the front, middle and rear sections of the anode plate and the cathode roller of the present invention have been reasonably designed. First, due to the high copper ion concentration in the electrolyte of the raw foil in the front section, the large anode area and large pole distance are used to achieve the regulation of current density (obtain a relatively small current density) and obtain raw foil of target thickness; secondly, the copper ion concentration of the electrolyte of the raw foil in the middle section decreases after consumption, so the minimum anode area and cathode anode pole distance are used to improve the current density, and the surface of the raw foil is roughened to produce copper buds, which provides a basis for the subsequent solidification and final production of copper nodules; finally, the copper ion concentration in the electrolyte of the raw foil in the rear section continues to decrease. In order to ensure that the current density is moderate, the copper buds obtained in the middle section are fixed on the surface of the raw foil to play a solidification role, and the anode area and pole distance are increased compared with the middle section.
[0031] The technical key of the present invention lies in the regulation of the anode area and the pole distance in the middle and rear sections. If the area of the middle section is too large, the roughened copper buds are high, the roughness is large after the subsequent solidification is small, and the solidification is insufficient, the copper nodules and the raw foil are not firmly connected, and copper powder is easily lost, and the anti-peeling strength is low. If the area of the middle section is too small, the roughened copper buds are few and low, and the subsequent solidification is to continue to deposit the copper layer, so the Rz will be small, the copper nodules are few, and the anti-peeling strength is low.
[0032] Furthermore, the temperature of the raw foil electrolyte is 49-51°C, and the circulation flow rate of the raw foil electrolyte is 20-50m 3 / h; the cathode roller rotation speed is 1-6m / min, the current density is 60-70A / dm 2 .
[0033] The fourth object of the present invention is:
[0034] Provided is an ultra-low profile electrolytic copper foil prepared by any of the above-mentioned preparation processes.
[0035] Furthermore, the ultra-low profile copper foil has a thickness of 12-50 μm, a roughness of the copper nodule surface of Rz≤2.0 μm, Ra≤0.35 μm, a room temperature tensile strength of 300-500 MPa, a room temperature elongation of 6-20%, and a peel strength of ≥1.0 N / mm.
[0036] Preferably, the ultra-low profile copper foil has a thickness of 18-35 μm.
[0037] The fifth object of the present invention is:
[0038] Provided is an ultra-low profile electrolytic copper foil prepared by any of the preparation processes or an application of the ultra-low profile electrolytic copper foil in a high-frequency and high-speed PCB board.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention improves the additives in the green foil electrolyte to form additives for ultra-low profile electrolytic copper foil, especially the brightener hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate cooperate with each other, and have a significant synergistic effect with the wetting agent and the leveling agent, thereby achieving the refinement of the green foil grains and the leveling of the profile, and providing a basis for the realization of ultra-low profile electrolytic copper foil;
[0041] (2) The concentration of brightener in the additive is further optimized, so that the grain refinement in the front stage of electrolysis is obvious, and the viscosity control of the wetting agent provides a better dispersion effect; in addition, the molecular weight distribution of the leveling agent ensures that the leveling effect can be fully exerted in the back stage of raw foil electrolysis and the roughening process; overall, it provides a guarantee for the production of low-profile electrolytic copper foil;
[0042] (3) In addition, the electrolytic copper foil prepared by compounding the additive with copper sulfate electrolyte and chloride ions also has excellent mechanical properties, such as high peel strength, tensile strength and elongation;
[0043] (4) The present invention not only obtains ultra-low profile electrolytic copper foil by compounding additives with copper sulfate electrolyte and chloride ions, combined with the design of the front, middle and rear sections of the anode plate, but also can replace the original two-step method for producing electrolytic copper foil, that is, the foil production and copper nodulation processes can be completed only in the foil production machine, which simplifies the equipment, shortens the production process, and greatly reduces the production cost of the ultra-low profile electrolytic copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram of the distribution of the anode plates in the anode tank of the present invention;
[0045] Figure 2 Scanning electron microscope image of the rough surface of the 18 μm electrolytic copper foil prepared in Example 1 of the present invention (without passing through the middle section and the rear section anode plate);
[0046] Figure 3 A scanning electron microscope image of the rough surface of the 18 μm electrolytic copper foil prepared in Example 1 of the present invention (after passing through the middle and rear anode plates). DETAILED DESCRIPTION
[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited.
[0048] Example 1
[0049] (1) adding sulfuric acid to a copper dissolving tank containing copper to dissolve the copper into a copper sulfate electrolyte, wherein the copper ion concentration is 70 g / L and the sulfuric acid concentration is 95 g / L; then purifying the copper sulfate electrolyte through multi-stage filtration and adding it to a high-level tank;
[0050] (2) Add additives (hexylbenzylamine salt, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, hydroxyethyl cellulose, polyethylene glycol and hydrolyzed collagen) and 38% concentrated hydrochloric acid to the copper sulfate electrolyte in the above-mentioned high-level tank, so that the concentration of hexylbenzylamine salt is 5 mg / L, the concentration of sodium polydisulfide propane sulfonate is 10 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 5 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 24 mg / L, the concentration of polyethylene glycol (3000-5000 Da) is 24 mg / L, the concentration of hydrolyzed collagen (molecular weight 2000-20000 Da) is 20 mg / L, and the concentration of chloride ions is 8 mg / L, and the mixture is evenly mixed to obtain a raw foil electrolyte;
[0051] (3) Inject the above-mentioned electrolyte solution into the anode tank of the foil machine (the anode plates of the anode tank of the foil machine are distributed as follows) Figure 1 As shown, the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate accounts for 4 / 5 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle anode plate accounts for 1 / 20 of the total area of the anode plate, is 4 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate accounts for 3 / 20 of the total area of the anode plate, is 8 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank), the raw foil electrolyte is heated to 50°C, and the circulation flow rate is 30m 3 / h, current is passed through the cathode roller of the foil machine and the cathode roller speed is set to 4m / min, and the current density is 70A / dm 2 , ultra-low profile copper foil is produced by continuous electrolysis.
[0052] Example 2
[0053] (1) adding sulfuric acid to a copper dissolving tank containing copper to dissolve the copper into a copper sulfate electrolyte, wherein the copper ion concentration is 75 g / L and the sulfuric acid concentration is 100 g / L; then purifying the copper sulfate electrolyte through multi-stage filtration and adding it to a high-level tank;
[0054] (2) Add additives (hexylbenzylamine salt, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, hydroxyethyl cellulose, polyethylene glycol and hydrolyzed collagen) and 38% concentrated hydrochloric acid to the copper sulfate electrolyte in the above-mentioned high-level tank, so that the concentration of hexylbenzylamine salt is 6 mg / L, the concentration of sodium polydisulfide propane sulfonate is 12 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 6 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 30 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000Da) is 30 mg / L, the concentration of hydrolyzed collagen (molecular weight 2000-20000Da) is 24 mg / L, and the concentration of chloride ions is 10 mg / L, and the mixture is evenly mixed to obtain a raw foil electrolyte;
[0055] (3) Inject the above-mentioned raw foil electrolyte into the anode tank of the raw foil machine (wherein the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate. The front anode plate occupies 4 / 5 of the total area of the anode plate, is 15 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle anode plate occupies 1 / 20 of the total area of the anode plate, is 5 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate occupies 3 / 20 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank), heat the raw foil electrolyte to 50°C, and circulate at a flow rate of 30m 3 / h, current is passed through the cathode roller of the foil machine and the cathode roller speed is set to 4m / min, and the current density is 70A / dm 2 , ultra-low profile copper foil is produced by continuous electrolysis.
[0056] Example 3
[0057] (1) adding sulfuric acid to a copper dissolving tank containing copper to dissolve the copper into a copper sulfate electrolyte, wherein the copper ion concentration is 65 g / L and the sulfuric acid concentration is 90 g / L; then purifying the copper sulfate electrolyte through multi-stage filtration and adding it to a high-level tank;
[0058] (2) Add additives (hexylbenzylamine salt, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, hydroxyethyl cellulose, polyethylene glycol and hydrolyzed collagen) and 38% concentrated hydrochloric acid to the copper sulfate electrolyte in the above-mentioned high-level tank, so that the concentration of hexylbenzylamine salt is 4 mg / L, the concentration of sodium polydisulfide propane sulfonate is 8 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 4 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 16 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000Da) is 16 mg / L, the concentration of hydrolyzed collagen (molecular weight 2000-20000Da) is 16 mg / L, and the concentration of chloride ions is 5 mg / L, and the mixture is evenly mixed to obtain a raw foil electrolyte;
[0059] (3) Inject the above-mentioned raw foil electrolyte into the anode tank of the raw foil machine (the structure of the anode tank of the raw foil machine is as follows) Figure 1 As shown, the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate accounts for 4 / 5 of the total area of the anode plate, is 5 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle anode plate accounts for 1 / 20 of the total area of the anode plate, is 2 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate accounts for 3 / 20 of the total area of the anode plate, is 5 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank), the raw foil electrolyte is heated to 50°C, and the circulation flow rate is 30m 3 / h, current is passed through the cathode roller of the foil machine and the cathode roller speed is set to 4m / min, and the current density is 70A / dm 2 , ultra-low profile copper foil is produced by continuous electrolysis.
[0060] Example 4
[0061] (1) adding sulfuric acid to a copper dissolving tank containing copper to dissolve the copper into a copper sulfate electrolyte, wherein the copper ion concentration is 65 g / L and the sulfuric acid concentration is 100 g / L; then purifying the copper sulfate electrolyte through multi-stage filtration and adding it to a high-level tank;
[0062] (2) Add additives (hexylbenzylamine salt, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, hydroxyethyl cellulose, polyethylene glycol and hydrolyzed collagen) and 38% concentrated hydrochloric acid to the copper sulfate electrolyte in the above-mentioned high-level tank, so that the concentration of hexylbenzylamine salt is 4 mg / L, the concentration of sodium polydisulfide propane sulfonate is 12 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 4 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 16 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000Da) is 30 mg / L, the concentration of hydrolyzed collagen (molecular weight 2000-20000Da) is 20 mg / L, and the concentration of chloride ions is 8 mg / L, and the mixture is evenly mixed to obtain a raw foil electrolyte;
[0063] (3) Inject the above-mentioned raw foil electrolyte into the anode tank of the raw foil machine (the structure of the anode tank of the raw foil machine is as follows) Figure 1 As shown, the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate accounts for 4 / 5 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle anode plate accounts for 1 / 20 of the total area of the anode plate, is 5 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate accounts for 3 / 20 of the total area of the anode plate, is 8 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank), the raw foil electrolyte is heated to 50°C, and the circulation flow rate is 30m 3 / h, current is passed through the cathode roller of the foil machine and the cathode roller speed is set to 4m / min, and the current density is 70A / dm 2 , ultra-low profile copper foil is produced by continuous electrolysis.
[0064] Example 5
[0065] (1) adding sulfuric acid to a copper dissolving tank containing copper to dissolve the copper into a copper sulfate electrolyte, wherein the copper ion concentration is 75 g / L and the sulfuric acid concentration is 90 g / L; then purifying the copper sulfate electrolyte through multi-stage filtration and adding it to a high-level tank;
[0066] (2) Add additives (hexylbenzylamine salt, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, hydroxyethyl cellulose, polyethylene glycol and hydrolyzed collagen) and 38% concentrated hydrochloric acid to the copper sulfate electrolyte in the above-mentioned high-level tank, so that the concentration of hexylbenzylamine salt is 6 mg / L, the concentration of sodium polydisulfide propane sulfonate is 8 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 6 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 30 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000Da) is 16 mg / L, the concentration of hydrolyzed collagen (molecular weight 2000-20000Da) is 20 mg / L, and the concentration of chloride ions is 8 mg / L, and the mixture is evenly mixed to obtain a raw foil electrolyte;
[0067] (3) Inject the above-mentioned raw foil electrolyte into the anode tank of the raw foil machine (the structure of the anode tank of the raw foil machine is as follows) Figure 1 As shown, the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate accounts for 4 / 5 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; the middle anode plate accounts for 1 / 20 of the total area of the anode plate, is 5 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate accounts for 3 / 20 of the total area of the anode plate, is 8 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode tank), the raw foil electrolyte is heated to 50°C, and the circulation flow rate is 30m 3 / h, current is passed through the cathode roller of the foil machine and the cathode roller speed is set to 4m / min, and the current density is 70A / dm 2 , ultra-low profile copper foil is produced by continuous electrolysis.
[0068] Comparative Example 1
[0069] The only difference from Example 1 is that the additives are different, specifically: the concentration of sodium polydisulfide propane sulfonate is 16.67 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 8.33 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 24 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000 Da) is 24 mg / L, and the concentration of hydrolyzed collagen is 20 mg / L.
[0070] Comparative Example 2
[0071] The only difference from Example 1 is that the additives are different, specifically: the concentration of hexylbenzylamine salt is 10 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 10 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 24 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000 Da) is 24 mg / L, and the concentration of hydrolyzed collagen is 20 mg / L.
[0072] Comparative Example 3
[0073] The only difference from Example 1 is that the additives are different, specifically: the concentration of hexylbenzylamine salt is 8.33 mg / L, the concentration of sodium polydisulfide propane sulfonate is 16.67 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 24 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000 Da) is 24 mg / L, and the concentration of hydrolyzed collagen is 20 mg / L.
[0074] Comparative Example 4
[0075] The only difference from Example 1 is that the concentrations of the ingredients in the additives are different, the concentration of hexylbenzylamine salt is 5 mg / L, the concentration of sodium polydisulfide propane sulfonate is 15 mg / L, the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 10 mg / L, the concentration of hydroxyethyl cellulose (aqueous solution with a mass concentration of 2% has a viscosity of 500-700 mPa.s at 20°C) is 2 mg / L, the concentration of polyethylene glycol (molecular weight 3000-5000 Da) is 5 mg / L, and the concentration of hydrolyzed collagen (molecular weight 2000-20000 Da) is 40 mg / L.
[0076] Comparative Example 5
[0077] The only difference from Example 1 is that the molecular weight of the hydrolyzed collagen in the additive as a leveling agent is 2000-8000.
[0078] Comparative Example 6
[0079] The only difference from Example 1 is that the molecular weight of the wetting agent polyethylene glycol in the additive is 6000-8000 DaDa.
[0080] Comparative Example 7
[0081] The only difference from Example 1 is that the anode cell structure is different, specifically: the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate occupies 4 / 5 of the total area of the anode plate, is 5 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode cell; the middle anode plate occupies 1 / 20 of the total area of the anode plate, is 10 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate occupies 3 / 20 of the total area of the anode plate, is 5 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode cell.
[0082] Comparative Example 8
[0083] The only difference from Example 1 is that the anode cell structure is different, specifically: the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate occupies 3 / 5 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode cell; the middle anode plate occupies 1 / 10 of the total area of the anode plate, is 4 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate occupies 3 / 10 of the total area of the anode plate, is 8 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode cell.
[0084] Comparative Example 9
[0085] The only difference from Example 1 is that the anode cell structure is different, specifically: the anode plate consists of a front anode plate, a middle anode plate and a rear anode plate, wherein the front anode plate occupies 4 / 5 of the total area of the anode plate, is 10 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode cell; the middle anode plate occupies 3 / 20 of the total area of the anode plate, is 4 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; the rear anode plate occupies 1 / 20 of the total area of the anode plate, is 8 mm away from the cathode roller, and is located at the end where the cathode roller leaves the anode cell.
[0086] Test Example 1: Copper Nodule Surface Roughness Detection
[0087] Detection method: (1) The rough surface of the electrolytic copper foil obtained by the front anode plate and the rough surface of the electrolytic copper foil obtained by the complete front, middle and rear anode plates prepared in Example 1 were characterized by scanning electron microscopy. The results are shown in Table 1. Figure 2 and Figure 3 .
[0088] Depend on Figure 2 and Figure 3 It can be seen that the rough side of the electrolytic copper foil that has not been treated with the middle and rear anode plates has a relatively smooth surface; after passing through the middle and rear anode plates, the copper nodules on the surface of the raw foil are firm, and the copper nodules are uniform in shape, size, distribution, and flatness.
[0089] (2) Refer to GB / T 5230-2020 Electrolytic Copper Foil for Printed Boards and use SJ-210 roughness tester to test the Rz value and Ra value of the treated surface. The specific test results are shown in Table 1 below.
[0090] Table 1 Copper nodule surface roughness results
[0091]
[0092]
[0093] Test Example 2: Peel Strength Test
[0094] Detection method:
[0095] (1) Refer to GB / T 5230-2020 Electrolytic Copper Foil for Printed Boards. After FR4 prepreg is pressed, peel test is performed using a universal mechanical testing machine.
[0096] (2) Copper powder shedding: Place the rough surface of the filter paper in contact with the rough cured surface of the copper foil, place a 200g weight on the other side of the filter paper, and evenly drag the filter paper for 50cm. Observe the copper powder on the rough surface of the filter paper and determine the grade. (Evaluation criteria for the powder shedding grade: Grade O: no copper powder shedding, Grade 1: a small amount of copper powder shedding, Grade 2: obvious copper powder shedding).
[0097] The thickness of the copper foil used in the test is 18 microns. The specific test results are shown in Table 2 below.
[0098] Table 2 Peel strength results
[0099]
[0100]
[0101] Test Example 3: Tensile Strength and Elongation Test
[0102] Test method: Test according to the method of GB / T 5230-2020 "Electrolytic Copper Foil for Printed Boards". The specific test results are shown in Table 3 below.
[0103] Table 3 Room temperature tensile strength and elongation at break results
[0104] Tensile strength / MPa Elongation at break % Example 1 451 12.4 Example 2 454 12.0 Example 3 458 12.8 Example 4 434 12.5 Example 5 449 12.2 Comparative Example 1 388 5.7 Comparative Example 2 431 6.2 Comparative Example 3 426 6.0 Comparative Example 4 382 7.2 Comparative Example 5 441 11.4 Comparative Example 6 422 6.9 Comparative Example 7 457 12.3 Comparative Example 8 413 10.4 Comparative Example 9 435 11.9
[0105] It can be seen from the above results that the electrolytic copper foil prepared by the electrolyte containing the additive of the present invention and the preparation process of the present invention not only has excellent low profile, with a surface roughness of Rz≤2μm, Ra≤0.35μm; but also has good mechanical properties, with a peel strength of ≥1N / mm 2, room temperature tensile strength ≥430MPa, elongation at break ≥12.0%. Therefore, it is widely used in high-frequency and high-speed PCB boards.
[0106] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. An additive for ultra-low profile electrolytic copper foil, characterized in that: The invention comprises the following components: a brightener, a wetting agent and a leveling agent; the brightener is hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate; the wetting agent is hydroxyethyl cellulose and polyethylene glycol; and the leveling agent is hydrolyzed collagen.
2. The additive for ultra-low profile electrolytic copper foil according to claim 1, characterized in that: The mass ratio of the brightener, wetting agent and leveling agent is 1:(2-2.5):1; the mass ratio of the hexylbenzylamine salt, sodium polydisulfide propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate is (4-6):(8-12):(4-6); the mass ratio of the hydroxyethyl cellulose and polyethylene glycol is (16-30):(16-30).
3. The additive for ultra-low profile electrolytic copper foil according to claim 1, characterized in that: The viscosity of the 2% hydroxyethyl cellulose aqueous solution at 20° C. is 500-700 mPa.s; the molecular weight of the polyethylene glycol is 3000-5000 Da; and the molecular weight of the hydrolyzed collagen is 2000-20000 Da.
4. An electrolyte for ultra-low profile electrolytic copper foil, characterized in that: The invention comprises the following components: a copper sulfate electrolyte, chloride ions and the additive for ultra-low profile electrolytic copper foil according to any one of claims 1 to 3.
5. The electrolyte for ultra-low profile electrolytic copper foil according to claim 4, characterized in that: include: Copper ion 65-75g / L, sulfuric acid 90-100g / L, chloride ion 5-10mg / L, hexylbenzylamine salt 4-6mg / L, sodium polydisulfide propane sulfonate 8-12mg / L, sodium N,N-dimethyldithiocarboxamide propane sulfonate 4-6mg / L, hydroxyethyl cellulose 16-30mg / L, polyethylene glycol 16-30mg / L and hydrolyzed collagen 16-24mg / L.
6. A process for preparing an ultra-low profile electrolytic copper foil, characterized in that: The following steps are involved: (1) mixing a copper sulfate electrolyte, chloride ions and an additive to obtain an electrolyte for ultra-low profile electrolytic copper foil; (2) The electrolyte for ultra-low profile electrolytic copper foil is injected into the anode tank, and the anode plate is immersed in the electrolyte for ultra-low profile electrolytic copper foil. Current is passed through the cathode roller for continuous electrolysis to obtain the ultra-low profile electrolytic copper foil.
7. The preparation process according to claim 6, characterized in that: The anode plate comprises a front anode plate, a middle anode plate and a rear anode plate; The front anode plate occupies 4 / 5 of the area of all anode plates, is 5-20 mm away from the cathode roller, and is located at the end where the cathode roller just enters the anode tank; The middle anode plate occupies 1 / 20 of the area of all anode plates, is 2-5 mm away from the cathode roller, and is between the front anode plate and the rear anode plate; The rear anode plate occupies 3 / 20 of the area of all anode plates, is 6-10 mm away from the cathode roller, and is located at the end of the cathode roller away from the anode tank.
8. The preparation process according to claim 6, characterized in that: The electrolyte temperature for the ultra-low profile electrolytic copper foil is 49°C-51°C, and the circulation flow rate is 20-50m 3 / h; the cathode roller rotation speed is 1-6m / min, the current density is 60-70A / dm 2 .
9. The ultra-low profile electrolytic copper foil prepared by the preparation process according to any one of claims 6 to 8, characterized in that: The ultra-low profile copper foil has a thickness of 12-50 μm, a roughness of the copper nodule surface of Rz≤2.0 μm, Ra≤0.35 μm, a room temperature tensile strength of 300-500 MPa, a room temperature elongation of 6-20%, and a peel strength of ≥1.0 N / mm.
10. Use of the ultra-low profile electrolytic copper foil prepared by the preparation process according to any one of claims 6 to 8 or the ultra-low profile electrolytic copper foil according to claim 9 in high-frequency and high-speed PCB boards.
Citation Information
Patent Citations
Nano-roughening electrolyte, method and product for ultra-low profile electrolytic copper foil
CN114318429B
Cited By
Electronic circuit copper foil and preparation method thereof
CN121087571A
Preparation method and application of electronic foil capable of providing high response
CN121381103A